Effects of Precipitants on Fischer-Tropsch Synthesis Over Co-Ru-Al2O3 Catalysts - Liu, Yan; Jia, Litao; Liu, Yachun; Hou, Bo; Li, Debao (Asian Journal of Chemistry, 2015)
In this work, the effects of precipitants on the physicochemical properties of the precursors, alumina, catalysts and the corresponding catalytic performance for Fischer-Tropsch synthesis were investigated systematically. Furthermore, the relations between pores size distribution of alumina, cobalt particle sizes and catalytic performance for Fischer-Tropsch synthesis were studied thoroughly. It was found that Boehmite (g-AlOOH) could be prepared by using ammonia or ammonium bicarbonate as precipitants, respectively, while the ammonium aluminium carbonate hydroxide (AACH) could be prepared from precipitating ammonium carbonate. Different alumina were obtained by roasting the prepared g-AlOOH and AACH, respectively. The pores size distribution of alumina were tuned by different precipitants and thus the cobalt particle sizes and the reduction behaviours of catalysts supported on the corresponding alumina could be regulated simultaneously.